PID Controller System Analysis on Automatic Voltage Regulator (AVR) for Regulating Excitation Voltage of a 3-Phase Synchronous Generator - Andi Krismanto M. David Panggabean; Haris Gunawan; Muhammad Erpandi Dalimunthe (Jurnal Multidisiplin Sahombu, 2025)
In power generation, voltage stability is a very important thing to consider because it can affect the electrical system. Changes in the output voltage of a generator are influenced by various factors including dynamic load and magnetic amplifier voltage (excitation voltage). In this final project, a 3-phase synchronous generator excitation voltage control system is created to maintain the stability of the generator voltage according to its rating of 380 volts. By implementing a PID controller, the size of the excitation voltage can be adjusted by changing the duty cycle of the PWM for switching the IGBT in the DC-DC converter power circuit of the buck-boost converter type. With the PID controller parameters Kp = 3, Ki-0.001, Kd = 0.001 and the excitation voltage that can be provided by the power circuit up to 130 volts dc, the system can be stable when there is a change in load. The recovery time to reach steady state is 1.3 seconds when loaded and 1.1 seconds when the load is removed.